Rendered Services and Dysservices of Dairy Farming to the Territories: A Bottom-up Approach in European Atlantic Area - C. Perrot; H.J. Ferguson; M. Mulholland; A. Brown; C. Buckley; J. Humphrey; K. Scully; M. Dorigo; P. Legrain; T. Bodin; O. Girma; P. Merino; et al. (Journal of Human, Earth, and Future, 2022)
The Dairy-4-Future project focuses on improving the sustainability of dairy farming in the UK, Ireland, France, Spain, and Portugal. Improvement in dairying sustainability can be achieved by supporting and expanding the positive impacts and services that dairy farming has upon, and offer to, the local communities and by reducing the disservices, or negative impacts associated with dairying. To create a qualitative identification of a relevant, ranked list of items or issues associated with dairying in each territory in the project, interactive workshops with local stakeholders were organized in each regional case study. Stakeholders identified positive or negative impacts of local dairy farming on their territories, broken down into four specific categories: provisioning (e.g., food), rural vitality, environmental quality, cultural heritage, and quality of life. A total of 165 services and 135 dysservices were identified, balanced across the four categories. From these services and dysservices, groupings showed correlations between items and/or territories (for example, between Northern Ireland and Cornwall; Southern Ireland and Normandy; Galicia and Brittany). The impact of farm system type, specifically grassland, played a strong role in the linking of services and dysservices.